A practice of ultra-fine tailings disposal as filling material in a gold mine. (1st July 2017) - Deng, D.Q.; Liu, L.; Yao, Z.L.; Song, K.I.-I.L.; Lao, D.Z.
Abstract: A practice of cemented backfill technology with ultra-fine tailings in a gold mine was comprehensively presented, and a series of tests were conducted in accordance with the peculiar properties of ultra-fine tailings and the mining technology conditions. The test results show that, the tailings from Shuiyindong Gold Mine have a great grinding fineness, with the average particle diameter 22.03 μm, in which the ultra-fine particles with the diameter below 20 μm occupying 66.13%. The analysis results of chemical components of tailings indicate that the content of SiO2 is relatively low, i.e., 33.08%, but the total content of CaO, MgO and Al2 O3 is relatively high i.e., 36.5%. After the settlement of 4–6 h, the tailing slurry with the initial concentration of 40% has the maximum settling concentration of 54.692%, and the corresponding maximum settling unit weight is 1.497 g/cm 3 . During the field application, the ultra-fine tailings and PC32.5 cement were mixed with the cement-tailings ratios of 1:3–1:8, and the slurry concentration of 50 wt% was prepared. Using the slurry pump, the prepared cemented backfill slurries flowed into the goaf, and then the strength of the cemented backfill body met the mining technique requirements in Shuiyindong Gold Mine, where the ore body has a smooth occurrence, with the average thickness of approximately 2 m and the inclination angle ranging from 5 to 10°. Highlights: Taking the goaf as the tailing dam to dispose the ultra-fine tailings. A large number of concrete columns can be replaced by the cemented tailing backfill body. The cemented backfill slurry with ultra-fine tailings is optimal when the concentration is approximately 50%. The risk of tailings dam break can be significantly reduced.